The patient’s profile of envenomation by venomous animals in the Federal District of Brazil between 2007 and 2015: a cross sectional study - Leite, Isac César Roldão; Margoto, Rebeca Marques; Xavier, Edgard Albernaz; Borges, Thatyane Costa; Pinto, Valéria Cardoso (Revista de Medicina e Saúde de Brasília, 2019)
Introduction: Injuries caused by venomous animals are frequent in all emergency departments. Incident rates have risen sharply over the years in Brasília-DF, varying according to the patient’s gender, age group, race, case and its consequences. Methods: This cross-sectional study analyzed 5,663 cases reported to the Ministry of Health – by the Information System on Diseases of Compulsory Declaration – between 2007 and 2015. Were analyzed 2957 for scorpions, 907 for snakes, 815 for bees, 453 for spiders, 419 for other animals (e.g. caterpillars, ants, wasps, beetles, centipedes) and 112 notifications whose victims could not identify the animal, but reported the bite and showed symptoms consistent with a venomous animal’s injury. Results: The economically active population was the most affected, as well as people of mixed race. Regarding the severity of the cases, 9.8% were considered severe, and 0.14% of the patients died. The mortality rate was 0.33% for snakes, 0.25% for bees, 0.22% for spiders and 0.07% for scorpions. When each animal was analyzed, the data were different both in the profile of the patients and in the genus of the animals involved. Accidents with scorpions accounted for 52.2% and prevailed in the female gender, with snakes accounting for 16% of the cases and prevailing in males, as well as spiders (8%), bees (14.4%) and other animals. Conclusions: The genus of snakes and spiders differed from the reports of other states, presenting a unique characteristic for the population of Brasília-DF. This study demonstrates the need for epidemiological assessments of major accidents with venomous animals for better distribution of specific serum and to optimize the identification of animals in cases where they were not identified by the victims.